Avaliação dos resultados dos modelos fleuriet e EVA® em cooperativas agropecuárias do Estado do Rio Grande do Sul - Grabin, Raquel (2005)
This thesis presents a study concerning the application and the analysis of Fleuriet Model and the model based on aggregate economic value. Fleuriet Model is the result from studies that were developed in 70 s decade in Brazilian firms, aiming to create techniques to obtain a financial management approach according to the Brazilian situation. By the consideration of re-arrangements on account s rubrics in balancesheets, elaborated according to society legislation, is possible to reach indices as treasure balance (TB), floating capital (FC) and necessity of floating capital (NFC), that configurate the base to the model TB = FC NFC. Those indices attest the financial profile under a dynamic focus (a firm in activity, not on static s conditions, has active money to pay the inactive, as the traditional analyses does). Since 80´s decade, a new rule to measure firm s performance consists to increase the value to shareholders, bringing out the evaluation based on aggregate economic value. Through this model, the emphasis is that, in fact, there are just one real profit, if so, operational results can cover total capital costs, including third capital and own capital. Model s application and research, and its relationship were based on the follow question: Gaúchas farming cooperatives societies could achieve operational results to present indices of performance which reflect the ability of financial balance of firm s dynamic and also generate economic value? This is a scientific research that use empiric and analytic qualitative methodology, through a no-experimental research or ex-post-fact research and statistic technique denominated not-parametric co-relation analyses, independents variables are TB, FC and NFC and only one dependent variable, which is the aggregate economic value. Tests were made on an intentional sample from 51 co-operative societies. Research result, considering the sample, shows that: 1) Financial performance, achieved from Fleuriet Model, attributed an unsatisfactory situation to the larger number of cooperatives societies. Positive NFC is not enough positive to supply firm s recourses requested to positive financing of NFC; 2) Economic performance presented a positive economic result, meaning that on the time period analyzed it kips stable to the grater number of those co-operatives; 3) co-relation treatment of data showed that economic result has more significance as the financial variables FC and NFC, because of TB variable presents non co-relation with EVA.